A Novel Healthcare Application for Hospital Bed Booking System (International Journal of Innovative Research in Computer Science & Technology, 2022)
With the increasing need for more better  way to consume a service during the Covid-19 pandemic,  as well as the need of more flexible way to register for the  beds in the hospitals, this paper introduces a Web  Application which is shaped to provide easy access to book  a bed in the hospital for the needy. This framework connects  the consumer to an online interface to register themselves  and book a bed on their name and hospitals to register  themselves and provide their details providing a time  efficient way to ease the efforts. It securely maintains the  data of users in a database working behind.
Keywords: Medical Tool; Hospital Bed Booking